The Launch of the Sheep Fattening Community of Practice (CoP) in North Shewa - Ekule, Muluken; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2022)
A report on the launch of the sheep-fattening community of practice (CoP) in North Shewa.